Role of “Sural Sparing” Pattern (Absent/Abnormal Median and Ulnar with Present Sural SNAP) Compared to Absent/Abnormal Median or Ulnar with Normal Sural SNAP in Acute Inflammatory Demyelinating Polyneuropathy - Surpur, Spurthi Sunil; Govindarajan, Raghav (Frontiers in Neurology, 2017)
Abstract: Background: Sural sparing defined as absent/abnormal median sensory nerve action potential amplitude (SNAP) or absent/abnormal ulnar SNAP amplitude with a normal sural SNAP amplitude is thought to be a marker for inflammatory demyelinating polyneuropathies. Objective: If sural sparing pattern specifically defined as absent/abnormal median and ulnar SNAP amplitude with normal sural SNAP amplitude (AMUNS) is sensitive and specific as compared to either absent/abnormal median and normal sural (AMNS) or absent/abnormal ulnar and normal sural(AUNS) for AIDP, CIDP and select non-diabetic axonopathies (AX) and diabetic neuropathies (DN). Method: Retrospective analysis from 2001-2010 on all newly diagnosed AIDP, CIDP, select non-diabetic axonopathies (AX) and diabetic neuropathies (DN). Results: There were 20 AIDP and 23 CIDP. 20 AX and 50 DN patients between 2009 and 2010 were included as controls. AMUNS was seen in 65% of AIDP, 39% CIDP compared with 10% of AX and 6% for DN with sensitivity of 51%, specificity of 92% whereas the specificity of AMNS/AUNS was 73% and its sensitivity was 58%. If a patient has AMUNS they are > 12 times more likely to have AIDP (p < 0.001). Conclusion: Sural sparing (AMUNS) is highly specific but not sensitive as compared to either AMNS or AUNS in AIDP but does not add to sensitivity or specificity in CIDP.